La cromatografía en capa fina: una alternativa vigente en la industria farmacéutica - Vallejo-Rosero, Yeraldin Johana (2021)
Thin-layer chromatography (TLC) emerged in the '50s, receiving great acceptance in its early years thanks to its versatility and efficiency. However, advances in new technologies caused thin layer chromatography to be progressively replaced, which is why we are looking for ways to couple TLC to more sophisticated and robust techniques in order to maintain its validity in the market. Nowadays, TLC is a technique that, when well-managed, allows the determination of purity and identification of raw materials of numerous drugs according to pharmacopoeia specifications, besides being used in rapid analysis for the detection of drugs and analyses of varied complexity. In the present assay, it will be demonstrated that TLC is a versatile, accessible and safe technique to perform chemical analyses with high performance if a basic knowledge and expertise for its execution are taken into account. d expertise for its execution is taken into account.